A novel isoflurane anesthesia induction system for raccoons - Kevin T. Bentler; Daniel N. Gossett; J. Jeffrey Root (Wildlife Society Bulletin)
Abstract We developed a novel small‐volume (24‐L) conical‐shaped isoflurane anesthesia induction chamber for use in a den chamber and tested it along with 3 conventional stand‐alone induction chambers (2 clear acrylic plastic chambers and a cylindrical‐shaped chamber) to determine utility for daily short‐duration manipulations of captive raccoons (Procyon lotor). Although the conventional chambers were valuable, the majority of inductions were performed using the cone chamber in a pen setting. With the novel device, we were able to minimize the need for pre‐anesthetic handling of animals and eliminate the need for injectable anesthesia agents. As a result, side effects normally associated with injectable agents were avoided. Mean anesthesia induction time using the cone chamber was 3.4 min (SD = 0.90). When used as designed, conventional chambers worked well, with induction times ranging from 2.7 min to 5.4 min. Because the stand‐alone chambers were not reliant upon den chambers for use, they may provide greater utility for field work. The conical‐shaped induction chamber, however, provides an option for safe short‐duration anesthetization of captive raccoons and could perhaps be used with other species and in other research settings. Published 2012. This article is a U.S. Government work and is in the public domain in the USA.